Influence of Supervision Factor on Role Difficulties Among Counsellor Trainees in UNIMAS - Nor Mazlina, Ghazali; Lee, M.F.; Wan Jaafar, W.M.; Anuar, Ayob (Academic Research Publishing Group, 2018)
Counsellor trainees have to play many roles simultaneously during supervision. Although all the roles and expected behaviour are well-defined, counsellor trainees find it hard to acquire and learn all the roles since all the expectations from the roles come at the same time, causing role difficulties. Role difficulties refer to role conflict and role ambiguity. Presence of role difficulties highly associated with to work-related anxiety, dissatisfaction with clinical work and supervision as well, shown by previous studies. This is a correlational research with quantitative nature. 85 counsellor trainees who under practicum supervision from UNIMAS will be recruited as respondents, by using stratified random sampling. The data collected will be analyzed using Pearson Product-Moment Correlation Coefficient and Multiple Regression. There are four (4) research instruments being used. Role Conflict and Role Ambiguity Inventory (RCRAI) is used to measure role difficulties, Counselling Self-estimate Inventory (COSE) is used to measure the level of self-efficacy, Trainee Anxiety Scale (TAS) is used to measure the level of anxiety and Supervisory Working Alliance Inventory – Trainee (SWAI – T) is used to measure the level of working alliance during supervision. The finding of the research showed that there is no significant relationship between supervision factors and role difficulties. There is also no significant influence of supervision factors on role difficulties. Moreover, anxiety showed r(88) = 0.46, p < 0.05, weak positive relationship with role difficulties and statistically significant F(1,86) = 22.40, p < .05, and accounted for approximately 21% of the variance of role difficulties. Selfefficacy showed r(88) = -0.43, p < 0.05 weak negative relationship with role difficulties and statistically significant F(1,86) = 19.92, p < .05, accounted for approximately 19% of the variance of role difficulties. Working alliance showed r(88) = -0.26, p < 0.05 weak negative relationship with role difficulties and statistically significant F(1,86) = 7.80, p < .05, accounted for approximately 8.0% of the variance of role difficulties. The implications of the research were able to expand and further support the Role Theory and Social Cognitive Model of Counselor Training (SCMCT) in which the findings explained the role problems in supervision context and further supported selfefficacy as the main determinant in effective counselling process. The research also provided practical implication in which the supervisor could be more aware of cognitive and emotional development of counselor trainees. Future researchers are recommended to (1) Recruit supervisors as respondents; (2)Include more supervision factors; (3)Choose suitable instruments and (4)Consider qualitative research.